Codesign of food system and circular economy approaches for the development of livestock feeds from insect larvae - Jagtap, Sandeep; Garcia-Garcia, Guillermo; Duong, Linh; Swainson, Mark; Martindale, Wayne (MDPI, 2021)
Processes that utilise low-value wastes and convert them to high-value food ingredients systemically add value across commercial operations. Current common disposal options include use as animal feed, anaerobic digestion, composting, incineration, and the worst-case options of landfill and wastewater disposal. The pressure is acute with food manufacturers needing to align with the UN Sustainable Development Goals and reach targets of zero waste to landfill. This research identifies black soldier fly larvae as a bioreactor that converts most food waste into high-value feed materials. Production of larvae and the regulatory framework for their use as animal feed is being assessed in several nations. The requirement to understand the availability of feedstocks for larvae production and the capability to establish feedstock supply chains was tested in this study using geographical information system and life cycle assessment methodologies, providing new research insights for resource utilisation in a circular economy.
Keywords: waste valorisation; aquaculture; poultry; food waste; circular economy; black soldier fly larvae